2020
DOI: 10.1111/cen.14194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous and intermittent aerobic physical training on hormonal and metabolic profile, and body composition in women with polycystic ovary syndrome: A randomized controlled trial

Abstract: ObjectiveTo evaluate the effects of continuous (CA) and intermittent (IA) aerobic training on hormonal and metabolic parameters and body composition of women with polycystic ovary syndrome (PCOS).DesignProspective, interventional, randomized study.MethodsRandomized controlled training (RCT) with sample allocation and stratification into three groups: CAT (n = 28) and IAT (n = 29) training and no training [control (CG), n = 30]. Before and after 16 weeks of intervention (CAT or IAT) or observation (CG), hormona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 42 publications
0
67
0
Order By: Relevance
“…In two studies (Almenning et al, 2015; Aktaş et al, 2019) [ 22 , 23 ], the values of TG, total cholesterol, and LDL-C decreased, while HDL-C levels increased. In a study by Ribeiro et al (2020) [ 26 ], the results revealed little evidence that HIIT could cause significant changes in these parameters.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In two studies (Almenning et al, 2015; Aktaş et al, 2019) [ 22 , 23 ], the values of TG, total cholesterol, and LDL-C decreased, while HDL-C levels increased. In a study by Ribeiro et al (2020) [ 26 ], the results revealed little evidence that HIIT could cause significant changes in these parameters.…”
Section: Resultsmentioning
confidence: 98%
“…Only one study (Faryadian et al, 2019) [ 24 ] did not analyze the pre- and post-intervention anthropometric indices of women with PCOS. However, four studies (Lopes et al, 2018; Aktaş et al, 2019; Ribeiro et al, 2019, 2020) [ 22 , 25 , 26 , 27 ] observed a significant decrease in BMI and WHR values after HIIT intervention. In two studies (Almenning et al, 2015; Samadi et al, 2019) [ 23 , 28 ], the percentage of fat or fat mass decreased significantly in the group that performed HIIT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations